2018
DOI: 10.1177/1049732318765720
|View full text |Cite
|
Sign up to set email alerts
|

Rural Postpartum Women With Substance Use Disorders

Abstract: The incidence of perinatal opioid use and neonatal withdrawal continues to rise rapidly in the face of the growing opioid addiction epidemic in the United States, with rural areas more severely affected. Despite decades of research and development of practice guidelines, maternal and neonatal outcomes have not improved substantially. This focused ethnography sought to understand the experience of accessing care necessary for substance use disorder recovery, pregnancy, and parenting. Personal accounts of 13 rur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 54 publications
(64 reference statements)
3
45
0
Order By: Relevance
“…Injecting drug use has been shown to be stigmatizing in many studies (Lloyd, 2013; Radcliffe & Stevens, 2008; Rhodes, Briggs, Kimber, Jones, & Holloway, 2007). Internalizing of guilt, described by Goffman (1973) and shown to be significant in the choice of treatment provider for pregnant drug users (Kramlich, Kronk, Marcellus, Colbert, & Jakub, 2018), was shown to be important in this study as well. Confidence in future sexual relationships was affected, though not for two sex workers.…”
Section: Discussionsupporting
confidence: 60%
“…Injecting drug use has been shown to be stigmatizing in many studies (Lloyd, 2013; Radcliffe & Stevens, 2008; Rhodes, Briggs, Kimber, Jones, & Holloway, 2007). Internalizing of guilt, described by Goffman (1973) and shown to be significant in the choice of treatment provider for pregnant drug users (Kramlich, Kronk, Marcellus, Colbert, & Jakub, 2018), was shown to be important in this study as well. Confidence in future sexual relationships was affected, though not for two sex workers.…”
Section: Discussionsupporting
confidence: 60%
“…Concerning gender differences, pregnant women experienced an advantage when attempting to obtain treatment. Related to substance use treatment, a previous study identified that rural women who experienced lengthy delays gained immediate treatment access upon becoming pregnant (Kramlich et al, 2018). Related to OUD, because MAT with buprenorphine or methadone is known to reduce maternal substance abuse and improve health outcomes for the mother and the unborn child (Klaman et al, 2017; Short et al, 2018), public efforts to expand access to MAT have been initiated for this specific population (Short et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has documented the importance of the patient–provider relationship in sustaining substance use treatment, with respect, empathy, and inclusion cited as essential therapeutic aspects (Kramlich et al, 2018). Findings presented here align with this work; participants highlighted these same values as vital in their MAT provider relationships, emphasizing how these factors were critical to creating the sense of safety and a platform for controlling their own recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Young et al (2015) conducted a literature review of rural community characteristics that could pose barriers to addiction recovery. Kramlich et al (2018) studied new mothers recovering from opioid use disorder in a rural area of the northeastern United States. Palombi et al (2019) conducted focus groups in northern Minnesota and in the upper peninsula of Michigan comparing individuals in early recovery and individuals in long-term recovery with regard to their access to “recovery capital,” a term describing resources that support addiction recovery.…”
mentioning
confidence: 99%
“…To varying degrees, these studies described obstacles to recovery in rural communities, but they also highlighted community strengths. Obstacles cited in these studies included high rates of poverty, transportation difficulties (Grant, 2007; Kramlich et al, 2018; Paterno et al, 2019; Veysey et al, 2010), a lack of community education, poor employment prospects after treatment (Grant, 2007; Veysey et al, 2010), a lack of access to specialized training for treatment providers (Grant, 2007; Young et al, 2015), difficulties accessing treatment (Grant, 2007; Kramlich et al, 2018; Young et al, 2015), social isolation (Veysey et al, 2010), a rural subculture of drug and alcohol use (Haight et al, 2009; Palombi et al, 2019), negative social support (Haight et al, 2009; Palombi et al, 2019; Veysey et al, 2010), and shame and stigma (Haight et al, 2009; Kramlich et al, 2018; Milofsky et al, 1993; Paterno et al, 2019; Veysey et al, 2010; Young et al, 2015). Meanwhile, the strengths of rural communities documented in these studies included access to nature (Milofsky et al, 1993); presence of treatment/drug court (Haight et al, 2009; Palombi et al, 2019); high quality and supportive health care providers (Kramlich et al, 2018); individual factors, such as self-reliance, resilience, positive attitude, maintenance of self-care, and social support from friends, family, and community (Haight et al, 2009; Palombi et al, 2019; Paterno et al, 2019); and, within the recovery community, accurate knowledge of, and willingness to help others with addiction (Veysey et al, 2010).…”
mentioning
confidence: 99%